Growing - finishing rations supplemented with zinc - proteinate - Koch, B.A.; Kropf, Donald H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The need for zinc in swine rations has been firmly established. Likewise the inter-relationships between dietary zinc and other minerals, especially calcium, have been well authenticated. However, there are still many unanswered questions concerning zinc and its place in the swine diet.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; Rations; Growing-finishing rations; Proteinate